Mother's Insight Regarding The Magnitude Of Parenting Communication - Yunike Yunike; Ira Kusumawaty (LAFADZ JAYA Publisher, 2022)
The optimal development of adolescents depends on the harmony of family communication, especially mothers as caregivers. Disputes between mothers and adolescents often occur and trigger fights and adolescent aggressive behavior that stretches family interactions. Communication contributes significantly to the development of teenage behavior; it can be explored based on the mother's experience as a caregiver. This study examines in-depth mothers' experiences in communicating with their adolescent children. Participants in this qualitative study using a phenomenological approach were mothers who lived with their teenage children, a total of 11 participants. The determination of participants was done by applying a purposive sampling technique. The conclusion of the number of samples is based on the saturation of the results of in-depth interviews conducted using video call technology. The Colaizzi method with the Haase adaptation was applied in analyzing the results of in-depth interviews that had been recorded to make it easier when compiling the transcript. Four themes have been generated in this study: The fabric of family love as a communication goal, undeniable dependence on communication, Vulnerability to give each other space to face communication challenges and the need for space and time to explore the importance of good communication. To ensure the trustworthiness of the research results, peer debriefing and member checking are carried out. It is necessary to have a common perception between mothers and adolescents in understanding the importance of Communication and instilling family commitments consistently by paying attention to the youth's freedom of opinion which must be optimally utilized according to the developmental tasks of adolescence.